2015
DOI: 10.1074/jbc.m114.618124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Gene Characteristics of Antibodies with Cofactor-induced HIV-1 Specificity

Abstract: Background: Normal immune repertoires have a fraction of cofactor-binding antibodies. Results: Heme exposure results in acquisition of reactivity to gp120 HIV-1 in 24% of antibodies in a seronegative immune repertoire; these antibodies have less mutated variable regions. Conclusion: Human immune repertoires contain high frequency of antibodies with cofactor-induced antigen specificities. Significance: This work enhances understanding of molecular features of heme-sensitive Abs and their contribution to diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 66 publications
6
34
0
Order By: Relevance
“…Likewise, exposure of purified pooled human IgG to haem leads to the acquisition of a considerable reactivity to many prototypical autoantigens used as targets for the diagnosis of autoimmune diseases [100][101][102] . Further investigations revealed that the interaction of human antibodies with haem induces a diversification in reactivity not only toward autoantigens but also toward pathogen-derived antigens 95,103,104 . It is noteworthy that binding affinities for the antigens recognized by haem-exposed IgG are substantial 105 .…”
Section: [H2] Use Of Non-protein Cofactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, exposure of purified pooled human IgG to haem leads to the acquisition of a considerable reactivity to many prototypical autoantigens used as targets for the diagnosis of autoimmune diseases [100][101][102] . Further investigations revealed that the interaction of human antibodies with haem induces a diversification in reactivity not only toward autoantigens but also toward pathogen-derived antigens 95,103,104 . It is noteworthy that binding affinities for the antigens recognized by haem-exposed IgG are substantial 105 .…”
Section: [H2] Use Of Non-protein Cofactorsmentioning
confidence: 99%
“…Binding analyses of repertoires of human monoclonal antibodies revealed that, depending on the studied antigen, the fraction of IgG that acquire novel antigen-binding specificities after contact with haem ranges between 9 and 24% 103,104 . Of note, the repertoire analyses demonstrated that haem-sensitive IgG had significantly lower number of somatic mutations in the genes encoding their V regions as compared to IgG that did not change their specificity upon exposure to haem 103,104 .…”
Section: [H2] Use Of Non-protein Cofactorsmentioning
confidence: 99%
“…Aside from inducing a pro‐thrombotic phenotype and activating complement heme inhibits ADAMTS‐13 activity, or activation of coagulation cascade . It also modifies the spectrum of recognized antigens by a particular fraction of immunoglobulins in the circulation . Thus, hemolysis is a supplemental actor, which participates in the definition of TMA, may act as a secondary hit, since others events had preceded it to induce the initial thrombus formation, causing erythrocytes rupture and heme release.…”
Section: Endothelial Cells As a Target In Ahusmentioning
confidence: 99%
“…204 It also modifies the spectrum of recognized antigens by a particular fraction of immunoglobulins in the circulation. 201,205 Thus, hemolysis is a supplemental actor, which participates in the definition of TMA, may act as a secondary hit, since others events had preceded it to induce the initial thrombus formation, causing erythrocytes rupture and heme release. By amplifying complement activation and prothrombogenic traits, heme creates a positive feedback loop that exacerbates endothelial activation.…”
Section: Redundancy Of the Aggression Makes The Diseasementioning
confidence: 99%
“…Therefore, heme as a key player in initiating or mediating distinct processes in connection with a viral infection needs to be considered as well. This can be exemplified with the interaction of heme with e.g., Zika, Chikungunya, and HIV-1 viruses (Gupta et al, 2015;Lecerf et al, 2015;Assunção-Miranda et al, 2016;Neris et al, 2018).…”
Section: Resultsmentioning
confidence: 99%